CHALLENGES IN THE CLOUD COMPUTING MODEL OF RESOURCE MANAGEMENT ISSUES SUCH AS SERVICE LEVEL AGREEMENTS AND SERVICES MODEL - Mohammed Tuays AlMuqati (International Journal of Research Science and Management, 2018)
Cloud computing has recently emerged as a new model for hosting and delivering services over the internet. Cloud computing has many advantages, such as the ability to increase capacity or add capabilities without the need to invest in new infrastructure. It can also fulfill technological requirements in a fast and automated manner. In recent years, cloud computing has changed the IT industry; in fact, it is one of the industry’s fastest growing phenomena. However, as more information about people and businesses becomes available in the cloud, concerns about the safety of this environment will increase. In addition, some challenges to the use of this service exist. This paper presents the results of a survey about cloud computing and outlines the main concepts of the technology along with examples of appropriate usage. It also discusses resource management issues such as service level agreements and highlights the challenges faced by users when choosing cloud computing services.